2014
DOI: 10.3390/ijms15035045
|View full text |Cite
|
Sign up to set email alerts
|

A Caspase-Dependent Pathway Is Involved in Wnt/β-Catenin Signaling Promoted Apoptosis in Bacillus Calmette-Guerin Infected RAW264.7 Macrophages

Abstract: Apoptosis of alveolar macrophages following Mycobacterium tuberculosis infection have been demonstrated to play a central role in the pathogenesis of tuberculosis. In the present study, we found that Wnt/β-catenin signaling possesses the potential to promote macrophage apoptosis in response to mycobacterial infection. In agreement with other findings, an activation Wnt/β-catenin signaling was observed in murine macrophage RAW264.7 cells upon Mycobacterium bovis Bacillus Calmette-Guerin (BCG) infection at a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
5
48
0
Order By: Relevance
“…In agreement with our results, a current investigation demonstrated that Wnt/beta-catenin signaling possesses the potential to promote macrophage apoptosis in response to mycobacterial infection (Wu et al, 2014). Notably, the activation of Wnt/beta-catenin signaling was able to increase apoptosis in BCG-infected mouse macrophagelike Raw 264.7 cells in part by a mitochondria-dependent apoptosis pathway (Wu et al, 2014). Furthermore, immunoblotting analysis indicated that Wnt/beta-catenin signaling induced cell apoptosis partly through a caspase-dependent apoptosis pathway by downregulation of the anti-apoptotic protein Mcl-1 and up-regulation of pro-apoptotic proteins Bax and cleaved-caspase-3, as well as by the enhancement of caspase-3 activity in BCG-infected RAW264.7 cells (Wu et al, 2014).…”
Section: Figsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, a current investigation demonstrated that Wnt/beta-catenin signaling possesses the potential to promote macrophage apoptosis in response to mycobacterial infection (Wu et al, 2014). Notably, the activation of Wnt/beta-catenin signaling was able to increase apoptosis in BCG-infected mouse macrophagelike Raw 264.7 cells in part by a mitochondria-dependent apoptosis pathway (Wu et al, 2014). Furthermore, immunoblotting analysis indicated that Wnt/beta-catenin signaling induced cell apoptosis partly through a caspase-dependent apoptosis pathway by downregulation of the anti-apoptotic protein Mcl-1 and up-regulation of pro-apoptotic proteins Bax and cleaved-caspase-3, as well as by the enhancement of caspase-3 activity in BCG-infected RAW264.7 cells (Wu et al, 2014).…”
Section: Figsupporting
confidence: 93%
“…Moreover, the interaction of co-stimulatory molecules B7.1 and B7.2 on antigen-presenting cells with CD28 on T cells is essential for optimal activation of antigen recognizing T-cells. In agreement with our results, a current investigation demonstrated that Wnt/beta-catenin signaling possesses the potential to promote macrophage apoptosis in response to mycobacterial infection (Wu et al, 2014). Notably, the activation of Wnt/beta-catenin signaling was able to increase apoptosis in BCG-infected mouse macrophagelike Raw 264.7 cells in part by a mitochondria-dependent apoptosis pathway (Wu et al, 2014).…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study revealed that downregulating Wnt and CTNNB1 expression increased Bax protein expression in HCT-116 cells. Wu et al (24) reported that the Wnt/CTNNB1 signaling pathway promoted apoptosis, and enhanced CASP3 function and Bax protein expression in Bacillus Calmette-Guerin vaccine-infected RAW264.7 macrophages. A previous study indicated that the Wnt/CTNNB1 signaling pathway may promote the proliferation and maintain the undifferentiated state in stem/ancestral cells of the bottom of the intestinal crypt (25).…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, exogenous WNT3A decreased tumor necrosis factor (TNF) and IL-6 expression by Mycobacterium bovis Bacillus Calmette-Guérin-infected RAW264.7 cells, reduced TNF release from M tuberculosis-infected murine primary macrophages, and induced IL-10 and transforming growth factor b expression by M tuberculosis-infected dendritic cells. 18,22,23 It is important to note that although recombinant WNT proteins are invaluable tools in many models, they may contain unrelated agonists for TLRs, 24 which clouds the interpretation of studies using these protein preparations in TLR-bearing cells. Although an increasing number of in vitro studies affirm contributions of WNT proteins to cell-specific cytokine responses, there is limited understanding of how the concerted action of WNT proteins shapes inflammatory responses in vivo.…”
Section: Introductionmentioning
confidence: 99%